Effectiveness of aged graffiti cleaning technologies on cultural heritage granite - Gomes, Vera Rute Soares (2018)
Graffiti paintings, as an act of vandalism, are one of the most severe threats to Cultural Heritage stone. The cleaning is expensive and may induce chemical and physical damages tom the stone. Graffiti is often executed in surfaces without anti-graffiti protection and in real practice are only removed after long periods of environmental exposure, leading to their interaction with the environmental agents and with the stone substrate. This dissertation intents to study to what extent the exposure to polluted environments will affect the graffiti removal, in order to provide relevant elements for future interventions in Cultural Heritage. Two sets of comparative studies were conducted, on unaged and on artificially aged samples (in a climatic chamber with SO2). Four graffiti aerosol paints were applied on an Iberian Peninsula granite, Rosa Porriño. Different cleaning procedures were applied: two chemical methods, four mechanical methods and a laser based-method. Microscope techniques, chemical and physical analytic techniques were used in order to firstly asses the characterization of unaged and aged paints and secondly to evaluate the cleaning performances based on the graffiti extraction level and induced harmful effects. The obtained results showed that the chemical and laser cleaning performance is associated to the binder composition of the paints (alkyd or polyethylene resins). It must also be pointed out the role of SO2 in the cleaning performance for all the cleaning methods. After ageing, the paints became more difficult to clean, presenting higher global colour changes, residue percentages and the surfaces became more water repellent. The best cleaning performances were achieved with the potassium hydroxide based chemical cleaner AGS 600® and the mechanical Hydrogommage® with silicon based abrasive. Finally, some futures research lines are pointed out.